2013
DOI: 10.1155/2013/953123
|View full text |Cite
|
Sign up to set email alerts
|

Access to Basic HIV-Related Services and PrEP Acceptability among Men Who Have sex with Men Worldwide: Barriers, Facilitators, and Implications for Combination Prevention

Abstract: Introduction. Men who have sex with men (MSM) are disproportionately impacted by HIV globally. Easily accessible combination HIV prevention strategies, tailored to the needs of MSM, are needed to effectively address the AIDS pandemic. Methods and Materials. We conducted a cross-sectional study among MSM (n = 3748) from 145 countries from April to August 2012. Using multivariable random effects models, we examined factors associated with acceptability of preexposure prophylaxis (PrEP) and access to condoms, lub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
117
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(127 citation statements)
references
References 39 publications
6
117
1
Order By: Relevance
“…In a previous study, we found that homophobia (perceptions of societal stigma associated with homosexuality), disclosure of sexual identity ("outness"), and service provider stigma were significantly associated with reduced access to HIV services. Conversely, we found that engagement in the local gay community and comfort with service providers were associated with increased access to services [22].…”
Section: Introductioncontrasting
confidence: 66%
See 1 more Smart Citation
“…In a previous study, we found that homophobia (perceptions of societal stigma associated with homosexuality), disclosure of sexual identity ("outness"), and service provider stigma were significantly associated with reduced access to HIV services. Conversely, we found that engagement in the local gay community and comfort with service providers were associated with increased access to services [22].…”
Section: Introductioncontrasting
confidence: 66%
“…The methods of the parent study, are published in detail elsewhere [22]. In summary, 6095 participants were recruited from 145 countries via networks of MSM community-based organizations and MSM online websites and list servs.…”
Section: Methodsmentioning
confidence: 99%
“…74 Further potentiating the biological drivers of HIV acquisition and transmission in all settings are the multiple forms of stigma affecting MSM that limit the provision and uptake of HIV prevention, treatment, and care services. [77][78][79] Exposure to stigma including culturally insensitive health workers can result in MSM avoiding HIV testing and other prevention services, limiting diagnosis and awareness of status. 78,[80][81][82] Even more acute, men who are aware of living with HIV may avoid HIV treatment altogether.…”
Section: -69mentioning
confidence: 99%
“…[77][78][79] Exposure to stigma including culturally insensitive health workers can result in MSM avoiding HIV testing and other prevention services, limiting diagnosis and awareness of status. 78,[80][81][82] Even more acute, men who are aware of living with HIV may avoid HIV treatment altogether. 83 Reduced utilisation of health and HIV services by MSM, due to enacted or perceived discrimination, limits knowledge of the risks of condomless anal intercourse and opportunities for access to prevention services.…”
Section: -69mentioning
confidence: 99%
“…Among studies focusing on low-income and middle-income countries, MSM participants from South Africa, Uganda, Brazil, Peru, China, India, Kenya, Malaysia, Myanmar, Thailand and Vietnam were surveyed ( [14][15]). In most studies, awareness of PrEP was quite low and the average was 30%.…”
Section: Prep In Msmmentioning
confidence: 99%